Dependence of the skating and running performance from the explosive strength of lower limbs and dynamic balance of ice hockey players - Blanár, M.; Brodáni, J.; Czaková, M.; Kovácová, N. (Sport Science - International Scientific Journal of Kinesiology, 2020)
This work refers to the dependence of the skating and running performance from the explosive strength of lower limbs and dynamic balance of an ice hockey player in the youth category. We suppose that the performance in the skating and running tests is limited by some factors as the explosive strength of lower limbs and dynamic balance and they create differentiated hierarchy according to the test difficulty. The ice skating tests and running tests were put to the relationship analysis as the dependent variables. Independent variables were formed by tests of maximal muscle strength of lower limbs, vertical jump with and without countermovement, standing long jump, single leg lateral jump from left and right foot and the test of dynamic balance on the right and left foot. In determining the limiting factors of performance in skating and running tests, we are coming out of the multiple correlation and regressions analysis. For the reduction of indicators, the stepwise analysis was used. From explosive strength of lower limbs indicators has a decisive contribution to the explanation of skating and running performance the vertical jump with countermovement, standing long jump and test of muscle performance of lower limbs. Single leg jump tests had the smallest part in these indicators. Dynamic balance tests have an impact only in 5-10-5 meters running test. From all skating tests have the highest consistency with tests of explosive strength of lower limbs the 5-10-5 test, which was proven statistically (F = 10,490; p<0,01), by intercorrelation (p<0,05) and practically (f2 = 1,592). From all running tests, the highest consistency with tests of explosive strength has the run to 10 meters test, which was proven statistically (F = 9,181; p<0,01), by intercorrelation (p<0,05) and practically (f2 = 0,706). In both cases are the partial proportions in individual parameters in positive relation to the skating and running performance. The assumption about the impact of the explosive strength of lower limbs and dynamic balance to the performance in the skating and running tests has been confirmed in the vertical jump, maximal muscle performance and in the standing long jump. The differentiated hierarchy of factors according to the test difficulty and their performance in the ice or in dry land has been proven.